Challenges perceived by social workers to prevent FGM/C in Bavaria: a prospective, cross-sectional survey - N. Seifert; E. Mürdter; NC. Schmidt (BMC, 2024)
Abstract Background Worldwide, at least 230 million girls and women are affected by female genital mutilation/ cutting (FGM/C). FGM/C violates human rights and can cause irreparable harm and even lead to death. In 2022, more than 100,000 survivors of FGM/C lived in Germany, and more than 17,000 girls were considered at risk. Due to the increasing number, there is a need to improve the skills of professionals not only to treat FGM/C but also to prevent it, aiming to maintain or improve women's physical and mental health. However, previous studies mostly focused on health care providers, even though other professionals such as social workers, play an important role in the provision of sexual and reproductive health (SRH) care and are often the first point of contact. Therefore, the study's main objective was to understand challenges perceived by social workers in pregnancy counselling centres in the provision of good quality of SRH care for girls and women suffering from or endangered by FGM/C. Methods A quantitative self-administered cross-sectional online survey was sent by e-mail in 2021 to all pregnancy counselling centers in the German federal state of Bavaria. Results Among the 141 participants, 82% reported no or insufficient FGM/C knowledge and barriers to provide the best quality of care. The main findings were language obstacles (82.7%), perceived client's fear or shame (67.9%) and cultural difficulties (45.7%). Furthermore, participants also reported a lack of competence on the professional side (29.6%). Importantly, most participants (129 of 141; 92%) expressed interest in training. Conclusion Providing comprehensive good quality sexual and reproductive health care to women and girls affected from or endangered by FGM/C is challenging. The study revealed the importance of strengthening the skills of social workers and suggested the following strategies: (1) enhancing FGM/C knowledge and skills (including specialized competences e.g., in mental health) by improving training and information material for the target group, (2) improving referral pathways and addressing deficits in the existing care system (e.g. with health or legal institutions), and (3) developing trusting relationships with cultural (or traditional) mediators to build strong community networks.